Molybdenum Disulphide Precipitation in Jet Reactors: Introduction of Kinetics Model for Computational Fluid Dynamics Calculations - Michał Wojtalik; Krzysztof Wojtas; Weronika Gołębiowska; Maria Jarząbek; Wojciech Orciuch; Łukasz Makowski (Molecules, 2022)
In our previous work, we used the population balance method to develop a molybdenum disulphide kinetics model consisting of a set of differential equations and constants formulated to express the kinetics of complex chemical reactions leading to molybdenum disulphide precipitation. The purpose of the study is to improved the model to describe the occurring phenomena more thoroughly and have introduced computational fluid dynamics (CFD) modelling to conduct calculations for various reactor geometries. CFD simulations supplemented with our nucleation and growth kinetics model can predict the impact of mixing conditions on particle size with good accuracy. This introduces another engineering tool for designing efficient chemical reactors.